α-Hemihydrate calcium sulfate/n-hydroxyapatite combined with metformin promotes osteogenesis in vitro and in vivo - Liu, Sirui; Fu, Haojie; Lv, Yan; Jiao, Jing; Guo, Runying; Yang, Yanyu; Dong, Wenhang; Mi, Hongyan; Wang, Meiyue; Liu, Mengzhe; Li, Rui (Frontiers in Bioengineering and Biotechnology, 2022)
This study aimed to examine the effects of loading different concentrations of metformin onto an α-hemihydrate calcium sulfate/nano-hydroxyapatite (α-CSH/nHA) composite. The material characteristics, biocompatibility, and bone formation were compared as functions of the metformin concentration. X-ray diffraction results indicated that the metformin loading had little influence on the phase composition of the composite. The hemolytic potential of the composite was found to be low, and a CCK-8 assay revealed only weak cytotoxicity. However, the metformin-loaded composite was found to enhance the osteogenic ability of MC3T3-E1 cells, as revealed by alkaline phosphate and alizarin red staining, real-time PCR, and western blotting, and the optimal amount was 500 µM. RNA sequencing results also showed that the composite material increased the expression of osteogenic-related genes. Cranial bone lacks muscle tissue, and the low blood supply leads to poor bone regeneration. As most mammalian cranial and maxillofacial bones are membranous and of similar embryonic origin, the rat cranial defect model has become an ideal animal model for in vivo experiments in bone tissue engineering. Thus, we introduced a rat cranial defect with a diameter of 5 mm as an experimental defect model. Micro-computed tomography, hematoxylin and eosin staining, Masson staining, and immunohistochemical staining were used to determine the effectiveness of the composite as a scaffold in a rat skull defect model. The composite material loaded with 500 µM of metformin had the strongest osteoinduction ability under these conditions. These results are promising for the development of new methods for repairing craniofacial bone defects.